Numerical modelling of thermal regime of railway track - structure with thermal insulation (Styrodur) - Ižvolt, Libor; Dobeš, Peter; Holešová, Michaela; Navikas, Deividas (Journal of Civil Engineering and Management, 2021)
This paper presents the results of numerical modelling of the influence of various factors (geometrical layout of the structural layers of the railway track, climatic factors and ballast fouling) on the freezing of railway track structure with a built-in thermal insulation layer of extruded polystyrene (Styrodur). At the same time, the suitability and expediency of incorporating the thermal insulation layer at the sub-ballast upper surface level (i.e. below the rail ballast construction layer), or at the level of subgrade surface are discussed. Numerical modelling results in the main factors that should be taken into account in the dimensioning of the sub-ballast layers with a built-in thermal insulation layer. Based on the data on the depth of freezing of the railway track structure obtained from numerical modelling, a design nomogram for dimensioning was created and subsequently the influence of the changes of climatic characteristics on the freezing of the railway track structure was then mathematically expressed.